The Influence of Firm Size, Liquidity, Profitability, Business Risk, and Growth on Capital Structure in The Industrial Sector - Wenni Br. Tampubolon; Robinhot Gultom; Rintan Saragih (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study is to investigate and evaluate the impact of the following factors on the Debt to Equity Ratio (DER): the Degree of Operating Leverage (DOL), Return on Assets (ROA), Current Ratio (CR), Natural Logarithm of Total Assets (LnTA), and Sales Growth (SG). Since this kind of research is expressed in numerical values that reflect the size of the variables under study, it can be categorized as quantitative research, as previously explained. There were 95 research data points available for testing out of the total observations. Ln (Total Assets) has no influence on DER, CR has a negative effect on DER, ROA has no effect on DER, DOL has no effect on DER, and SG has no effect on DER, according to the results of the t-test hypothesis. The DER value is significantly impacted by Ln (Total Assets), CR, ROA, DOL, and SG all at the same time, according to the results of the F-test hypothesis. According to the coefficient of determination analysis, the R-square value is 0.201, or 20.1%, meaning that Ln (Total Assets), CR, ROA, DOL, and SG can account for 20.1% of the variation in DER. Other variables or circumstances influence the remaining 100% - 20.1% = 79.7%.